Plain old disrespect: Explorations of recognition and motivation in care work - Austen, Siobhan; Jefferson, Therese (Centre for Research in Applied Economics Working Paper Series, 2013)
Existing mainstream economic models for investigating care work have generated limited insights. In contrast, theory developed outside of mainstream economics, particularly theory that utilises feminist insights, appears contextually relevant to care work but is in a relatively early stage of development for application to empirical analysis. This paper considers appropriate models of care work situations, especially the motives for the performance of care work and the specific role played by ‘recognition’. We outline the experiences and perceptions of mature age Australian women who participated in a small exploratory study. We also report data derived from a subsequent survey of almost 4000 Australian aged care workers. We identify recognition as a factor that, thus far, has not been explicitly considered in the economics literature on the motivation for care work but which has the potential to inform strategies aimed at improving outcomes for care workers and care recipients.